A Descriptive Study of Nosocomial Infections in an Adult Intensive Care Unit in Fiji: 2011-12. (17th September 2014) - Naidu, Keshni; Nabose, Ilisapeci; Ram, Sharan; Viney, Kerri; Graham, Stephen M.; Bissell, Karen
Abstract : Nosocomial infections in an intensive care unit (ICU) are common and associated with a high mortality but there are no published data from the Oceania region. A retrospective study in Fiji's largest ICU (2011-12) reported that 114 of a total 663 adult ICU admissions had bacteriological culture-confirmed nosocomial infection. The commonest sites of infection were respiratory and bloodstream. Gram negative bacteria were the commonest pathogens isolated, especially Klebsiella pneumoniae (extended-spectrum β -Lactamase-producing), Acinetobacter, and Pseudomonas species. Mortality for those with a known outcome was 33%. Improved surveillance and implementation of effective preventive interventions are needed.